The possibilities to use public procurement as one of the instruments of implementation of sustainable development concept in republic of Lithuania - Tvaronavičienė, Agnė (Business: Theory and Practice, 2012)
Sustainable development is universal ideology, which must be implemented in all areas of public life. Public procurement is a universal procedure for purchasing the products required for the subjects of public administration. As a social system this institute is being influenced by various factors of its environments, but at the same time it may also influence the same elements. That’s why the public procurement worldwide is accepted as a public policy tool. The implementation of sustainable development concept is one of the areas where public procurement may be used as an effective tool promoting main ideas in economic, social and environmental aspects. Sustainable public procurement is a concept which has not been revealed in Lithuanian science yet. According to the research papers and legal acts of foreign countries, sustainability in public procurement refers to such aspects as best value for price, lowest price of all life circle, responsiveness for environmental issues and using of measures of social effects. The results of research reveal that the legal system of Lithuanian Republic contains certain manifestations of the use of public procurement to implement the sustainable development concept. Despite of the fact that the main legal acts regulating public procurement do not define the determination of sustainable public procurement, certain provisions empower the purchasing organizations to use environmental and social environments during the procurement procedures on its own initiative. Moreover, in recent years the imperative order to impose the part of annual procurement for social and environmental purposes is being fortified. However, the lack of clear and pointed towards effective achievement of the goals in the field of implementation of sustainable development concept in public policy was detected. In order to achieve more effective transplantation of sustainable development concept implementation in Lithuanian legal system, further researches of worldwide practice and modelling of transition of such practices into Lithuanian legal environment are required. Article in Lithuanian. Viešųjų pirkimų kaip vieno iš darniojo vystymosi koncepcijos įgyvendinimo instrumento naudojimo Lietuvos respublikoje galimybės Santrauka. Straipsnyje glaustai apžvelgiama darniojo vystymosi koncepcijos evoliucija, pagrindinės idėjos ir jų taikymo sritys, nagrinėjamos viešųjų pirkimų instituto galimybės būti vienu iš instrumentų įgyvendinant šią ideologiją. Taip pat, atskleidžiant darniųjų viešųjų pirkimų sampratą, peržvelgiama pasaulio valstybių patirtis šį institutą naudojant kaip priemonę darniojo vystymosi koncepcijai įgyvendinti. Siekiant nustatyti, ar esamu metu Lietuvos Respublikoje egzistuoja teisinės galimybės perkančiosioms organizacijoms vykdant viešuosius pirkimus aktyviai taikyti ekonominius, socialinius ir aplinkosaugos reikalavimus, kaip sudedamuosius darniojo vystymosi koncepcijos elementus, įvertinama, ar pasaulyje vyraujančios ideologijos įgyvendinimas yra skatinamas mūsų valstybės, nagrinėjama, kaip galiojantys nacionalinės teisės programiniai dokumentai ir teisės normų aktai reglamentuoja darnumo reikalavimų taikymą viešųjų pirkimų srityje. Reikšminiai žodžiai: darnusis vystymasis, darnieji viešieji pirkimai, socialiai orientuoti viešieji pirkimai, žalieji viešieji pirkimai, aplinkosaugos reikalavimai.